Utilization of location-based services for the design of agricultural sales applications - Taufik, Moch; Haviana, Sam Farisa Chaerul; Kurniadi, Dedy (Jurnal Transformatika, 2018)
Onion is one of the main income sectors in Brebes Regency, since most of Brebes area is rice field. Climate and soil type in Brebes is very suitable for onion cultivation plus onion has a high selling value compared to other agricultural products, it makes onion become the main choice of agricultural citizens. The magnitude of the red shadow from Brebes supplies 23% of national needs. One common problem that arises is how to bridge or facilitate farmers to offer their crops, and make it easier for buyers to locate farmers who sell their crops. One solution is the development of a system that can be an e-commerce web for a special sales promotion media for Gapoktan members (Combined Farmer Group) in Brebes District that will connect sellers and buyers online, and location search media for buyers to more easily find distribution location of the seller by using Location Based Service. Keywords: Location Based Service, Onion